Absolute quantification of 35 plasma biomarkers in human saliva using targeted MS. (January 2016) - Hirtz, Christophe; Vialaret, Jérôme; Nowak, Nora; Gabelle, Audrey; Deville de Périère, Dominique; Lehmann, Sylvain
Background: Although the use of human saliva for diagnosing disease has been known to be of great clinical potential, few attempts have been made so far to develop its use. In this work, we developed an MRM-MS approach for 35 plasma biomarkers using human saliva in a clinical environment.Methods & results: A 30-min micro LC–MS/MS run in MRM mode was conducted in order to quantify the 35 plasma proteins in human saliva. Sample preparation procedures were performed in quadruplicate and analyzed in duplicate. Results show that 32 of the 35 plasma proteins were quantified in human saliva using calibration curves in the 2- log10 dynamic ranges with excellent linearity.Discussion/conclusion: Our MRM method is compatible with routine measurements in daily clinical practice.